Research gender-sensitive manifestation of teens' disharmonious emotional state - Stepanenko, L. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article presents the problem of manifestation of negative emotional states of individual. There was researched peculiarities manifestations of emotional disharmonious states of adolescents (anxiety, aggression, frustration, depression, emotional instability and emotional discomfort). Performed comparative analysis from the standpoint of gender specific.
Keywords: psychological states; emotional states; disharmonious emotional states